Bleeding control in palliative care patients with the help of tranexamic acid - Geist, Marcus Julian Peter; Keßler, Jens; Frankenhauser, Susanne; Bardenheuer, Hubert J. (Journal of palliative care, 2017)
Background:Persistent bleeding is a common reason for admitting patients with advanced cancer to a palliative care unit. Several reports show a successful therapeutic use of the antifibrinolytic agent tranexamic acid in palliative care patients having hemorrhages. However, it is not administered routinely in severe bleeding situations in palliative care, and general dosing recommendations are unclear.Case Presentation:We report on 3 patients who were treated with tranexamic acid due to symptomatic hemorrhage complicating different malignant processes.Case Management and Outcome:A dosing regimen of 1000 mg intravenous tranexamic acid 3 times a day caused an arrest of bleeding in the reported patients within 2 to 3 days. Having controlled the acute bleeding, we continued with an oral administration of 3000 mg per day as maintenance dose.Conclusions:The described dosing regimen was effective in controlling the symptomatic bleeding of the reported patients. Further studies are needed to get evidence-based information on the optimal dosing regimen of tranexamic acid and to emphasize its significance in palliative medicine.